Investigating the production of a particulate plant-produced vaccine candidate against African horse sickness - Luhanga, Gloria (Department of Molecular and Cell Biology, 2022)
African horse sickness (AHS) is a non-communicable, infectious disease that affects equids and is mainly prevalent in sub-Saharan Africa. The disease has a major impact on the economy of the equine industry as well as an emotional impact on horse owners. There are nine known serotypes of African horse sickness virus (AHSV), which is spread by Culicoides midges. Currently, a multivalent live attenuated vaccine is the only vaccine licensed for use in South Africa. However, it has the inherent risk of reverting to virulence as well as the possibility of genome segment reassortment between vaccine and outbreak strains. Additionally, it is not DIVA compliant (cannot Differentiate between Infected and Vaccinated Animals). There is therefore a need for a safer and more cost-effective alternative vaccine to protect horses against AHSV. Virus-like particles (VLPs) that display antigens on their surface may be suitable vaccine platforms. One such display particle is the phage AP205 VLP, which is comprised of AP205 coat proteins. To aid antigen display, studies have utilized the SpyTag (ST) - SpyCatcher (SC) or “plug-and-display” system, a novel conjugation system used to display several antigens fused to AP205 VLPs. This study aimed at displaying the neutralizing epitope of AHSV serotype 5, known as the VP2 domain (dom) (873bp), on phage AP205 VLP particles using the SpyTag/SpyCatcher technology. The display particle vaccine candidates were produced in Nicotiana benthamiana plants. Firstly, AHSV 5 VP2dom was expressed by being linked to either the ST or SC peptide at its C-terminus. Recombinant pEAQ-AHSV 5-VP2dom ST and pEAQ-AHSV 5- VP2domSC plasmid constructs were constructed from the full-length pEAQ-AHSV 5-VP2- SpyTag and pEAQ-AHSV 5-VP2-SpyCatcher clones using in-fusion cloning. The ST/SC constructs were transformed into Stellar™ competent E. coli cells and thereafter into Agrobacterium tumefaciens AGL-1 cells. Expression time trials were conducted on plants infiltrated with the recombinant Agrobacterial strains to examine transient AHSV 5- VP2domST/SC small-scale expression. Expression was detected for AHSV 5 VP2domSC but not AHSV 5 VP2domST using guinea pig anti-AHSV 5 and rabbit antiST-AP205 sera. Secondly, the development of a particle display vaccine candidate was investigated by coupling AHSV 5 VP2domSC to plant-expressed ST-AP205 VLPs. Three coupling techniques, namely in vitro coupling of purified products, co-infiltration and co-purification, were deployed to determine the assembly of ST-AP205_AHSV 5 VP2domSC VLPs. In vitro coupling involved carrying out separate infiltrations and purification of pEAQ-STAP205 VLPs and pEAQ-AHSV 5 VP2domSC in plants and thereafter mixing the purified products. For co-infiltration, pEAQ-ST-AP205 VLPs and VP2domSC recombinant cultures were used together to infiltrate plants and the presence of complex formations was determined. During co-purification, the presence of coupled products was analysed following separate infiltration of plants with pEAQ-ST-AP205 and VP2domSC recombinant Agrobacterial strains; the homogenates were then incubated together at different VLP: antigen leaf:weight ratios. From the three coupling techniques, copurification at a 1:1 VLP: antigen ratio was identified as the best coupling approach based on the quality and quantity of particles visualised by electron microscopy. These findings indicate the potential of producing an AHSV vaccine candidate in plants, which is ultimately a safer and cheaper alternative to the currently-produced AHSV vaccine. Moreover, this preliminary data may pave the way for developing a vaccine that provides protection against all nine serotypes of AHSV by displaying VP2domSC for other serotypes on the ST-AP205 display particles.